Cultural values and technology adoption: A model comparison with university teachers from China and Spain. (May 2019) - Huang, Fang; Teo, Timothy; Sánchez-Prieto, José Carlos; García-Peñalvo, Francisco J.; Olmos-Migueláñez, Susana
Abstract: In this study, we investigated how certain cultural values influenced Chinese and Spanish university teachers' intentions to use technology. 426 Chinese university teachers and 404 Spanish university teachers participated in the study. The participants completed self-designed questionnaires based on Hofstede's cultural dimensions (individualism-collectivism, power distance, uncertainty avoidance and indulgence-constraint) as well as subjective norms and behavioural intention. We found consistent and significant relationships between subjective norms and behavioural intention in both the Spanish and Chinese samples. In addition, we found that the teachers' perceived cultural preferences influenced their subjective norms and intentions to use technology in both the Chinese and Spanish samples. However, the relationships between these variables were different in the Spanish and Chinese samples. In addition, we compared three models which were all theoretically reasonable to determine the model that best fitted the data. This study contributes to our understanding of how culture influences teachers' intentions to use technology in the contexts of Spain and China. Highlights: The influence of cultural values is assessed using three competing models. The models are tested using two samples of university teaches from China and Spain. The results provide evidence on how culture influences the adoption of technology.